Early Endothelial Dysfunction in Type 1 Diabetes Is Accompanied by an Impairment of Vascular Smooth Muscle Function: A Meta-Analysis - Lespagnol, Elodie; Dauchet, Luc; Pawlak-Chaouch, Mehdi; Balestra, Costantino; Berthoin, Serge; Feelisch, Martin; Roustit, Matthieu; Boissière, Julien; Fontaine, Pierre; Heyman, Elsa (Frontiers in Endocrinology, 2020)
Background. A large yet heterogenous body of literature exists suggesting that endothelial dysfunction appears early in type 1 diabetes, due to hyperglycemia-induced oxidative stress. The latter may also affect vascular smooth muscles (VSM) function, a layer albeit less frequently considered in that pathology. This meta-analysis aims at evaluating the extent, and the contributing risk factors, of early endothelial dysfunction, and of the possible concomitant VSM dysfunction, in type 1 diabetes. Methods. PubMed, Web of Sciences, Cochrane Library databases were screened from their respective inceptions until October 2019. We included studies comparing vasodilatory capacity depending or not on endothelium (i.e. endothelial function or VSM function respectively) in patients with uncomplicated type 1 diabetes and healthy controls. Results. Fifty-eight articles studying endothelium-dependant function, among which 21 studies also assessed VSM, were included. Global analyses revealed an impairment of standardised mean difference (SMD) (Cohen’s d) of endothelial function: −0.61 (95% CI −0.79, −0.44) but also of VSM SMD: −0.32 (95% CI −0.57, −0.07). The type of stimuli used (i.e. exercise, occlusion-reperfusion, pharmacological substances, heat) did not influence the impairment the vasodilatory capacity. Endothelial dysfunction appeared more pronounced within macrovascular than microvascular beds. The latter was particularly altered in cases of poor glycemic control (HbA1c > 67 mmol/mol (8.3%)). Conclusions. This meta-analysis not only corroborates the presence of an early impairment of endothelial function, even in response to physiological stimuli like exercise, but also highlights a VSM dysfunction in children and adults with type 1 diabetes. Endothelial dysfunction seems to be more pronounced in large than small vessels, fostering the debate on their relative temporal appearance.